Mixed non-specific vaginal infections: the experience with topical therapy - I.O. Borovikov; I.I. Kutsenko; V.P. Bulgakova; E.R. Rubinina; Kh.I. Gorring (РМЖ. Мать и дитя, 2020)
I.O. Borovikov, I.I. Kutsenko, V.P. Bulgakova, E.R. Rubinina, Kh.I. Gorring Kuban State Medical University, Krasnodar, Russian Federation Aim: to describe the experience with the topical treatment for mixed non-specific vaginal infections. Patients and Methods: this prospective study included 72 women (mean age 26.3±5.5 years) with mixed non-specific vaginal infections who received a vaginal capsule containing metronidazole and miconazole (at night for 10 days) followed by a probiotic containing L. casei rhamnosus Doderleini (intravaginally for 14 days). Vaginal microbiota was assessed by real-time PCR. The ratios of Lactobacillus spp. and anaerobic microbe concentrations and the total amount of opportunistic microflora were calculated. In addition, vaginal pH, Hay/Ison criteria, and the sensitivity of Candida spp. to antimycotics (NCCLS standards) were evaluated. When analyzing cellular composition, white blood cell count, epithelial cell count, total cell count, and cytological coefficient were measured. The efficacy was assessed 10 days and 1 month after the treatment. Results: the treatment resulted in the significant reduction in the clinical (both subjective and objective) symptoms of mixed non-specific vaginal infections, the improvement of vaginal discharge pH and the cellular composition of vaginal discharge and vaginal microbiocenosis. Microscopy with Hay/Ison criteria assessment demonstrated the normalization of Lactobacillus count and the reduction in the threshold of opportunistic microflora and Candida spp. Conclusions: our experience with the topical treatment for mixed non-specific vaginal infections using a drug containing metronidazole and miconazole has demonstrated high clinical (96%) and microbiological (97.4%) efficacy and safety as well as good treatment compliance. Keywords: mixed non-specific vaginal infection, decontamination, metronidazole, miconazole, vaginal microbiocenosis, bacterial dysbiosis. For citation: Borovikov I.O., Kutsenko I.I., Bulgakova V.P. et al. Mixed non-specific vaginal infections: the experience with topical therapy. Russian Journal of Woman and Child Health. 2020;3(4):221–227. DOI: 10.32364/2618-8430-2020-3-4-221-227.